Anticholinergic burden and clinical outcomes among older adults admitted in a tertiary hospital: a prospective cohort study - Pornkamol Tiranaprakij; Sahaphume Srisuma; Krongtong Putthipokin; Sirasa Ruangritchankul (PLoS ONE, 2025)
Background Anticholinergic medication use is associated with adverse clinical outcomes, especially in older adults. However, few studies have assessed the anticholinergic burden in the Thai geriatric population. Hence, we aimed to evaluate the impact of anticholinergic burden on clinical outcomes in older patients after discharge from the hospital. Methods A prospective cohort study was conducted between January 1 to December 31, 2023. The prescribed medications were assessed at admission and discharge to determine the anticholinergic cognitive burden (ACB) scores. Participants were classified into three groups according to the ACB score at discharge: none (score 0), moderate (score 1–2), and severe (score ≥ 3) anticholinergic burden. The Cox proportional hazard model was used to determine the marker risk of high anticholinergic burden to adverse outcomes. Results This study involved 290 older patients admitted to general internal medicine wards. At discharge, 37.9% (n = 110) of the patients had a high anticholinergic burden (ACB score ≥ 3), and 50% (n = 145) had a higher ACB score than at admission. The three most commonly prescribed anticholinergics at discharge were benzodiazepines (20.3%), corticosteroids (20.0%), and antihistamines (15.9%). During the one-year follow-up period, 16.6% (n = 48) of the patients died. The incidence rate of all-cause mortality in hospitalized older patients with an ACB score ≥ 3 was 0.65 cases per 1000-person day during a one-year follow-up period. After adjusting for potential factors, an ACB score of ≥ 3 at discharge was marginally associated with one-year mortality post discharge [hazard ratio: 2.98, 95% confidence interval (0.96–9.28)]. Conclusions The exposure to high anticholinergic burden (ACB scores ≥ 3) at discharge was slightly associated with an increased risk of one-year mortality post discharge. The cautious use of benzodiazepines may assist to reduce the anticholinergic burden in this vulnerable population.